Basis Data Semu Menggunakan Lembar Kerja Elektronik pada Sistem Otomatisasi Perkantoran - Feri Sulianta (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
The development of information technology nowadays encourages users to use the software appropriately so that commercial software can be maximally empowered that contribute to the efficiency and effectiveness of the job. To support its work, users use Microsoft's Microsof Excel Office Automation System worksheet commonly used by end users for clerical, repetitive and independent work. Microsoft Excel applications are generally used for office worker, clerical computation and users generally use only a portion of the features of some features owned by the application. In this case, the user can maximize the ability of Excel by creating an interactive pseudo database using only Microsoft Excel, so users can organize data with automated database schema. It is intended for time efficiency and also improves the data security factor of human error in handling data. Keywords: Office Automation System, Pseudo Database, Electronic Worksheet, Automatic